2017
DOI: 10.1177/0300060516676630
|View full text |Cite
|
Sign up to set email alerts
|

Proximal fibular osteotomy: a new surgery for pain relief and improvement of joint function in patients with knee osteoarthritis

Abstract: ObjectiveTo explore the effects of proximal fibular osteotomy as a new surgery for pain relief and improvement of medial joint space and function in patients with knee osteoarthritis.MethodsFrom January 2015 to May 2015, 47 patients who underwent proximal fibular osteotomy for medial compartment osteoarthritis were retrospectively followed up. Preoperative and postoperative weight-bearing and whole lower extremity radiographs were obtained to analyse the alignment of the lower extremity and ratio of the knee j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
109
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(125 citation statements)
references
References 8 publications
10
109
2
4
Order By: Relevance
“…). Recent published studies have consistently reported improvements in pain and function, as well as re‐adjustment of knee biomechanics and kinematics after proximal partial fibulectomy. The application of this procedure in treating medial compartment knee OA was rationalized by the theory of non‐uniform settlement of the tibial plateau, which contains two essential initiatives that work synergistically to exacerbate the varus deformity of the tibia: osteoporosis of the proximal tibia and lateral support provided by the fibula–soft tissue complex.…”
Section: Introductionmentioning
confidence: 99%
“…). Recent published studies have consistently reported improvements in pain and function, as well as re‐adjustment of knee biomechanics and kinematics after proximal partial fibulectomy. The application of this procedure in treating medial compartment knee OA was rationalized by the theory of non‐uniform settlement of the tibial plateau, which contains two essential initiatives that work synergistically to exacerbate the varus deformity of the tibia: osteoporosis of the proximal tibia and lateral support provided by the fibula–soft tissue complex.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [24] reported results on 46 patients who had undergone PFO with a follow-up of 12 months. No postoperative complications were found, and the duration of the procedure lasted 32 ± 9 min.…”
Section: Discussionmentioning
confidence: 99%
“…It was found in clinical studies of PFO that varus deformity improved following PFO [18,19,24]. When the continuity of the fibula is interrupted, the loads borne by the lateral column of the proximal tibia increases resulting in "settling" on the lateral side [21,24] (Fig.…”
Section: The Concept Of Non-uniform Settlementmentioning
confidence: 99%
“…Our group established the non‐uniform settlement theory by researching anatomy, radiology, biomechanics, and clinic. We proposed osteoporosis was the initial factor for causing force change.…”
Section: Discussionmentioning
confidence: 99%